A comparative study between a target controlled infusion (TCI) and manual controlled infusion (MCI) of propofol for sedation during cerebral protection in severe traumatic brain injured patients - Anuwar, Ahmad (2008)
Propofol is the commonest sedative agent used in traumatic brain injured (TBI) patient using manual controlled infusion (MCI) technique. The development of target controlled infusion (TCJ) technique has given a new dimension of propofol administration and it has never been tested in TBI patients. The aims of this study were to compare the effectiveness of different method of propofol infusion (TCI versus MCI) for sedation during cerebral protection in TBI patient in Neurosurgical Intensive Care Unit (NICU). Methodology In this prospective, double blinded, randomized controlled trial study, 50 patient who had traumatic brain injury with a Glasgow Coma Scale (GCS) between 3 to 8, age between 16 to 50 years old with no severe medical illness and undergoing craniotomy were randomized into two groups using block randomizations (25 patients in each group). However, one of the patients in MCI group had to be excluded due to very agitated state in spite of adequate sedation until the extend requiring muscle relaxant. During surgery, both groups received anesthesia with a standard protocol and the study started once patients admitted to Neuro ICU for cerebral protections. Sedations level was monitored using Bispectral index (BIS) monitor and Sedation Agitation Scale (SAS). BIS index of 60-70 and SAS score of 2-3 was considered as adequate sedation. Both groups used the same infusion pump which can operate either TCI or MCI and the drugs administrated via a dedicated central venous line lumen. Homodynamic parameters (blood pressure and heart rate ) and neurological parameters (intracranial pressure and cerebral perfusion pressure) were recorded, time and volume used to achieve BIS 70, total volume of propofol used for 24 hours and time taken to achieve BIS 90 after stopping infusion at the end of cerebral protection were measured. Fentanyl infusion at 1 meg/kg were given for pain relieve and was stopped four hours before the end of the study (24 hours). Results There are some significant differences between two modes of infusion. TCI mode achieved SIS 60-70 significantly faster than MCT with mean time 6.32 ± 2.88 minutes compared to MCI which is 19.71 ± 7.00 minutes. Time taken to recover from sedation to achieving BIS 90 was also significantly faster in TCI at 22.44 ± 11.50 minutes compared to MCI 57.29 ± 19.89 minutes. In view ofiCP, there was a significant difference between two modes but no significant difference in MAP and CPP Conclusion TCI mode of propofol is more effective in sedating neurotrauma patients as gives adequate sedation faster with a lesser volume and also faster recovery. It also lowers the Intracranial pressure (ICP) to less than 20rnmHg better than MCI.